A disruptura das democracias contemporâneas na era das redes tecnológicas e os impactos das fake news - Rossato, Gianna Bertolin (2022)
The first objective of this research is to define technological networks, presenting concepts and foundations of network theory through the study of the theories of Niklas Luhmann and Jürgen Habermas. Following this, an analysis is made of how data impacts people's lives today, with the development of algorithms that classify data and, consequently, individuals. The first chapter concludes by addressing the rights to privacy and intimacy, given that personal information is exposed in the use of data. It is also through the power over data that fake news has gained prominence. The following chapter proposes an examination of the online disinformation network, addressing freedom of expression, news control, and the right to truth. For this purpose, the doctrines of Pierre Levy, who studies the impacts of the internet on society, and Manuel Castells, with his theory of the interactive network society in the transmission of information, were primarily used. The final section examines the state of democracy, its minimum elements of existence, and fundamental rights from the perspective of the unregulated use of the internet. Furthermore, it highlights legislation on data protection and the draft law on fake news, as well as news related to the themes of this study. Thus, the investigation questions whether contemporary democracies are being disrupted, with an emphasis on Brazil and the United States of America, due to the emergence of technological networks and fake news. The relationship between the content of the investigation and the associated research line (Constitutional Jurisdiction and Democracy) is based on the theory of fundamental rights and the democratic regime. Methodologically, this research uses a deductive approach, a qualitative investigation, a basic nature, exploratory objectives, and a monographic method.